Clinical outcomes of polyvalent immunoglobulin use in solid organ transplant recipients: A systematic review and meta‐analysis – Part II: Non‐kidney transplant. Issue 7 (24th June 2019) - Bourassa‐Blanchette, Samuel; Patel, Vishesh; Knoll, Greg A.; Hutton, Brian; Fergusson, Nicholas; Bennett, Alexandria; Tay, Jason; Cameron, D. William; Cowan, Juthaporn
Abstract: Immunoglobulin (IG) is commonly used to desensitize and treat antibody‐mediated rejection in solid organ transplant (SOT) recipients. The impact of IG on other outcomes such as infection, all‐cause mortality, graft rejection, and graft loss is not clear. We conducted a similar systematic review and meta‐analysis to our previously reported Part I excluding kidney transplant. A comprehensive literature review found 16 studies involving the following organ types: heart (6), lung (4), liver (4), and multiple organs (2). Meta‐analysis could only be performed on mortality outcome in heart and lung studies due to inadequate data on other outcomes. There was a significant reduction in mortality (OR 0.34 [0.17‐0.69]; 4 studies, n = 455) in heart transplant with hypogammaglobulinemia receiving IVIG vs no IVIG. Mortality in lung transplant recipients with hypogammaglobulinemia receiving IVIG was comparable to those of no hypogammaglobulinemia (OR 1.05 [0.49, 2.26]; 2 studies, n = 887). In summary, IVIG targeted prophylaxis may decrease mortality in heart transplant recipients as compared to those with hypogammaglobulinemia not receiving IVIG, or improve mortality to the equivalent level with those without hypogammaglobulinemia in lung transplant recipients, but there is a lack of data to support physicians in making decisions around using immunoglobulins in all SOT recipients for infection prophylaxis.